Fetishism and the language commodity: a materialist critique. (November 2018) - Simpson, William; O'Regan, John P.
Abstract: Over the past 10 years, an emerging body of research in applied linguistics and linguistic anthropology has made the argument that recent global political-economic developments have led to the commodification of language. In focusing on how language is seen as a tradeable commodity, the process of commodification is portrayed as a principally discursive event, where value and commodity status are attributed to languages. However, the notion of both value and of commodities themselves as discursive matters stands in contrast to Marxist and classical political economy where commodities have value only insofar as they are congealed embodiments of human labour, expended in production processes where labour stands in relation to capital. In juxtaposing the 'language commodity' with the commodity of Marxist political economy, and in drawing on Marx's notion of commodity fetishism, we argue that though language may appear to be a commodity, it is not one, as language itself is not a product of labour. We conclude by discussing what a closer engagement with the more material concerns of production offer political economy approaches to language in addressing an 'ideal' and 'material' epistemological divide (Gal, 1989; Irvine, 1989; Friedrich, 1989; Shankar and Cavanaugh, 2012). Highlights: Language is not a commodity itself, but only appears as one through the fetishism of capitalism. Language is not produced or exchanged in the same way as commodities. Commodification and value should not be discussed in purely discursive terms. Greater consideration of the material concerns of contemporary capitalism is argued for.